Identification of PLOD Family Genes as Novel Prognostic Biomarkers for Hepatocellular Carcinoma - Yang, Bo; Zhao, Yonghui; Wang, Lan; Zhao, Yuanyuan; Wei, Lai; Chen, Dong; Chen, Zhishui (Frontiers in Oncology, 2020)
Background: Hepatocellular carcinoma (HCC) is one of the most common malignancies with rising incidence and persistently high mortality. Previous researches have demonstrated that some PLOD family members are associated with tumor progression and metastasis in most human cancers. However, the prognostic and biological roles of PLODs in HCC remain largely unknown. Methods: ONCOMINE, HPA, UALCAN, GEPIA, c-BioPortal, GeneMANIA, NetworkAnalyst, Metascape, DAVID 6.8, and TIMER were used to determine the prognostic values and biological function of PLOD family members in HCC. Results: The mRNA and protein expression patterns of PLOD family members were noticeably upregulated in HCC compared to normal tissue. The high expression levels of PLOD1 and PLOD2 genes were significantly correlated with higher tumor grades in HCC patients. In addition, the high expression levels of PLOD1-3 were remarkably associated with poor overall survival in HCC patients, while high PLOD1 and PLOD3 expression were markedly associated with worse disease-free survival. In the co-expression gene analysis, twenty genes were primarily associated with the differentially expressed PLOD family members in HCC cases. Through functional enrichment analysis, the biological functions of PLODs in HCC were mainly involved in collagen fibril organization, lysine degradation, collagen biosynthesis and modifying enzymes. Furthermore, the expression levels of PLOD1-3 were positively correlated with the activities of tumor-infiltrating immune cells, including macrophages, neutrophils, CD4+ T cells and dendritic cells. Besides, the expression levels of PLOD2 and PLOD3 were positively correlated with the infiltrating levels of B cells. Conclusions: The findings of this study could provide novel insights into the identification of prognostic biomarkers for HCC patients.